2015
DOI: 10.1186/s12864-015-1864-y
|View full text |Cite
|
Sign up to set email alerts
|

Andrographis paniculata transcriptome provides molecular insights into tissue-specific accumulation of medicinal diterpenes

Abstract: BackgroundKalmegh (Andrographis paniculata) has been widely exploited in traditional medicine for the treatment of infectious diseases and health disorders. Ent-labdane-related diterpene (ent-LRD) specialized (i.e., secondary) metabolites of kalmegh such as andrographolide, neoandrographolide and 14-deoxy-11,12-didehydroandrographolide, are known for variety of pharmacological activities. However, due to the lack of genomic and transcriptomic information, underlying molecular basis of ent-LRDs biosynthesis has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
57
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 67 publications
8
57
2
Order By: Relevance
“…From common backbones, diterpene scaffolds are often further modified to diterpenoids, prototypically by cytochrome P450 monooxygenases (CYPs), although 2‐oxoglutarate‐dependent dioxygenases (2OGDs) appear to play a role in certain cases as well (Swaminathan et al ., ; Wang et al ., 2012a; Kakizaki et al ., ; Xu and Song, ). Thus, although the biosynthesis of andrographolide and neoandrographolide is believed to rely on CYPs (Garg et al ., ; Cherukupalli et al ., ), 2OGDs may also play a role. In the A. paniculata genome, 278 CYP genes were found by automated matching to the relevant Hidden Markov Model (HMM), PF00067, with subsequent manual assignment to the appropriate CYP families (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…From common backbones, diterpene scaffolds are often further modified to diterpenoids, prototypically by cytochrome P450 monooxygenases (CYPs), although 2‐oxoglutarate‐dependent dioxygenases (2OGDs) appear to play a role in certain cases as well (Swaminathan et al ., ; Wang et al ., 2012a; Kakizaki et al ., ; Xu and Song, ). Thus, although the biosynthesis of andrographolide and neoandrographolide is believed to rely on CYPs (Garg et al ., ; Cherukupalli et al ., ), 2OGDs may also play a role. In the A. paniculata genome, 278 CYP genes were found by automated matching to the relevant Hidden Markov Model (HMM), PF00067, with subsequent manual assignment to the appropriate CYP families (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Root-specific co-expression of CDPS and KS, key enzymes for the committed step towards biosynthesis of diterpene alkaloids, is consistent with previous reports on the accumulation of aconitine-type metabolites in the roots of A. carmichaelii . Several studies have reported that CDPS is involved in the tissue-specific accumulation of diterpene alkaloids [ 48 , 49 ]. Two CDPSs have been reported in rice to be localized differentially owing to their distinct biological role, with high expression in the vascular bundle tissues for GA biosynthesis (OsCPS1) and epidermal cells for the biosynthesis of phytoalexins (OsCPS2), respectively [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since the last decade, different research groups have exploited these high throughput sequencing technology for better understanding of the molecular level information of various non model plant species such as Chickpea 17 , Cynara cardunculus 18 , lentil 19 , Centella asiatica 20 , Thlaspi arvense 21 , tomato 22 , Bupleurum chinens 23 , Cistus creticus 24 , Sesamum indicum L . 25 , Cucurbita pepo 26 , Camellia sinensis 27 , Camillia azalea 28 , Andrographis paniculata 29 , Asparagus racemosus 30 and many more. These studies provided us with much higher molecular level of information as compared to the past.…”
mentioning
confidence: 99%
“…It is well documented that the leaf and sheath tissues of C. witerianus contains high amount of essential oils but root tissue lacks 31 32 . Biosynthesis and accumulation of secondary metabolite are often tissue-specific, and related genes of enzymes and regulators also show organ- or tissue-specific expression patterns 29 30 . Therefore, we hypothesized that DEG analysis between these two tissues will give a better understanding about the genes involve in secondary metabolite pathway and their regulation.…”
mentioning
confidence: 99%